2016
DOI: 10.2147/copd.s116072
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the clinical characteristics and treatment outcomes of patients requiring hospital admission to treat eosinophilic and neutrophilic exacerbations of COPD

Abstract: PurposeWe compared the clinical characteristics and treatment outcomes of patients with eosinophilic and neutrophilic COPD exacerbations requiring hospital admission.Patients and methodsThis was a retrospective multicenter study performed between January 2010 and December 2014. In all, 1,688 COPD patients admitted via the outpatient clinics or emergency departments of six university hospitals were enrolled. The patients were grouped by complete blood counts: eosinophilic group, >2% peripheral blood eosinophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…18 Similarly, Kang suggested better pulmonary function, lower admissions to the ICU, and mortality in a group with eosinophil levels less than 2%. 19 Duman et al reported that shorter hospital stays and lower readmission rates were found in the group with eosinophilia, but no differences were found in six-month mortality. 20 Patients with AECOPD, and low (< 50/µL) eosinophil were strongly associated with longer median hospital stay (7 vs 4 days, P < 0.001), and lower 12-month survival (82.4% vs 90.7%, P < 0.028) than patients with high (> 150/µL) eosinophil counts.…”
Section: Introductionmentioning
confidence: 96%
“…18 Similarly, Kang suggested better pulmonary function, lower admissions to the ICU, and mortality in a group with eosinophil levels less than 2%. 19 Duman et al reported that shorter hospital stays and lower readmission rates were found in the group with eosinophilia, but no differences were found in six-month mortality. 20 Patients with AECOPD, and low (< 50/µL) eosinophil were strongly associated with longer median hospital stay (7 vs 4 days, P < 0.001), and lower 12-month survival (82.4% vs 90.7%, P < 0.028) than patients with high (> 150/µL) eosinophil counts.…”
Section: Introductionmentioning
confidence: 96%
“…62 Another retrospective Chinese case-control study 63 on hospitalized COPD patients also found no differences in WBC, neutrophil, and CRP levels between AECOPD þ CAP and AECOPD groups, although the percentage of neutrophils increased from baseline. Generally considered a marker of bacterial infection, 64 this increase was shown to be a protective factor for pneumonia, probably due to the early use of antibiotics that delayed progression in patients with AECOPD. 63 Of note, the level of D-dimer was higher for patients with AECOPD þ CAP and predicted the presence of CAP, 63 suggesting its potential utility as a diagnostic tool for identifying infection.…”
Section: Systemic Inflammatory Responsementioning
confidence: 99%
“…Hye et al investigated the importance of inflammatory markers to AECOPD pa-Open Journal of Respiratory Diseases tients required to hospital admission. [20] They conducted a retrospective study enrolled 1688 COPD subjects admitted to the outpatient and the emergency departments ( Table 2). According to their complete blood count, the patients were grouped into eosinophilic group (peripheral blood eosinophilia "PBE" > 2%) and neutrophilic group (Peripheral blood neutrophils "PBN" > 650 or leukocytes > 11.000/ml) and their clinical characteristics and treatment outcomes were compared.…”
Section: Peripheral Blood Eosinophilia and Aecopdmentioning
confidence: 99%